A molecular imaging analysis of Cx43 association with Cdo during skeletal myoblast differentiation. Issue 8 (29th August 2012) - Nosi, Daniele; Mercatelli, Raffaella; Chellini, Flaminia; Soria, Silvia; Pini, Alessandro; Formigli, Lucia; Quercioli, Franco
Abstract Cell‐to‐cell contacts are crucial for cell differentiation. The promyogenic cell surface protein, Cdo, functions as a component of multiprotein clusters to mediate cell adhesion signaling. Connexin 43, the main connexin forming gap junctions, also plays a key role in myogenesis. At least part of its effects is independent of the intercellular channel function, but the mechanisms underlying are unknown. Here, using multiple optical approaches, we provided the first evidence that Cx43 physically interacts with Cdo to form dynamic complexes during myoblast differentiation, offering clues for considering this interaction a structural basis of the channel‐independent function of Cx43. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)